MANAGEMENT OF PARTHENIUM HYSTEROPHORUS USING SUPPRESSIVE PLANTS - Ali, Sadiq; Khan, Ijaz Ahmad (Malaysian Journal of Science, 2017)
Parthenium hysterophorus; an invasive, noxious weed creates problem in field crops, pastures, waste lands and affects the fodder crops in Khyber Pakhtunkhwa, province of Pakistan. P. hysterophorus secretes allelochemicals to suppress the growth of neighboring plants. However, some crops have the ability to suppress the growth of numerous weeds. For this purpose field experiments were conducted at two different locations having variable climatic conditions to manage P. hysterophorus through some suppressive plants. The study revealed that sorghum, buffel grass, millet and maize showed good suppressive ability of P. hysterophorus weed biomass as compared to control which produced higher biomass at both field sites. However, at lower altitude site i.e Swabi, the highest P. hysterophorus dry biomass (340.45 g m-2) was recorded in moth bean plots, while at high altitude site (Haripur), the maximum P. hysterophorus dry biomass (384.80 g m-2) was found in mung bean plots. Moreover, at both sites, the sorghum, buffel grass, millet and maize plants reduced the P. hysterophorus growth up to 84.0%, 79.0%, 70.2% and 67.5%, respectively. Whereas mung bean and moth bean were found poor suppressive plants to reduce the growth of P. hysterophorus. Furthermore, the competitive ability of P. hysterophorus with other plants were climatic condition dependent as this weed poorly compete with the tested plants in the warmer climatic condition at Swabi site than the cooler area at Haripur site. Thus, it is to concluded that sorghum and buffel grass are better option to manage P. hysterophorus in the fields infested with invasive P. hysterophorus. Keywords: Parthenium, suppressive fodder plants, competition